2017
DOI: 10.1111/1365-2435.12999
|View full text |Cite
|
Sign up to set email alerts
|

Earthworms increase plant biomass more in soil with no earthworm legacy than in earthworm‐mediated soil, and favour late successional species in competition

Abstract: As ecosystem engineers, earthworms greatly affect plant communities. They create persistent soil structures enriched by nutrients that improve the conditions for plant growth and modify competition between plant species. We therefore hypothesized that earthworm activity would be more important in early stages of the primary succession, when the soil is not modified by earthworms, than in the late stages of the succession, when the soil is already improved by earthworms. On the other hand, earthworms also affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…pH and conductivity were determined in the same filtrate with a glass, potentiometric electrode. The data revealed that earthworm activity reduced the pH, increased the nitrate concentration, and tended to increase the soluble P concentration of the soil (Table ) which is in line with Mudrák and Frouz ().…”
Section: Methodssupporting
confidence: 85%
See 4 more Smart Citations
“…pH and conductivity were determined in the same filtrate with a glass, potentiometric electrode. The data revealed that earthworm activity reduced the pH, increased the nitrate concentration, and tended to increase the soluble P concentration of the soil (Table ) which is in line with Mudrák and Frouz ().…”
Section: Methodssupporting
confidence: 85%
“…Earthworms therefore have positive feedback effects on plant community composition and productivity (Thompson et al 1993, Scheu and Parkinson 1994, Brown et al 2000, Scheu 2003, Wurst et al 2005, Baker et al 2006, Roub ı ckov a et al 2009, Mudr ak et al 2012. Earlier field observation, and manipulation experiments, that was carried in the post-mining sites used in this study demonstrated a change of plant community following the earthworm colonization , Roub ı ckov a et al 2009, Mudr ak et al 2012, Mudr ak and Frouz 2018. Earthworm establishment in disturbed surfaces requires the amelioration of adverse conditions, for example, pH, stabilization of the physiochemical conditions in the soil, and availability of a suitable food supply (Curry 2004) which agrees with the reports of when earthworms colonize the post-mining area , Roub ı ckov a et al 2009, Mudr ak et al 2012.…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations